Chinese Movies and Dramas as a Medium for Teaching Mandarin Speaking Proficiency to Mandarin Language Learning Students at Universitas Sebelas Maret, Surakarta - Anjana, Regina Pravangasta Dyang; Basamah, Shofia Azra; Arini, Wulan; Maharani, Cristina (Confucius Institute Universitas Sebelas Maret, 2024)
Films and dramas have become one of the most powerful mediums in reflecting and shaping our perspective on various aspects of life and have long been recognized as an effective method in helping to improve students’ learning ability in learning and practicing foreign languages. Through the combination of audio, visual and narration, they not only create authentic communicative situations, but also allow students to learn the culture and social context in which the language is spoken. In Chinese language learning practice, Chinese movies and dramas are able to provide an interesting learning experience, not only as a fun medium but also greatly to improve listening, speaking skills as well as the addition of common vocabulary contained in movies and dramas. In the context of Mandarin Chinese, movies and dramas can be valuable tools in providing an introduction to pronunciation, tone, and intonation and emphasis in speaking. This study aims to explore the effectiveness of using Chinese films and dramas as learning media to improve Chinese speaking among Chinese language learning students at Universitas Sebelas Maret (UNS). The unit of analysis in this study is the students majoring in Mandarin at Universitas Sebelas Maret (UNS), who will be asked to complete a questionnaire regarding the impact of Chinese movies and dramas on their Mandarin language and speaking skills. The researcher wanted to understand the extent to which this approach can improve students’ speaking skills in Chinese and how students respond to this method. Theoretically, this study contributes to the language learning literature by providing insights into how audiovisual media can be effectively used in the context of foreign language education, specifically Mandarin language. Thus, this study aims to provide valuable insights for the development of more innovative and engaging learning strategies in the context of teaching Chinese in an academic setting.